2009
DOI: 10.1002/jrs.2546
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of structural disorder in ZnO nanopowders

Abstract: Raman scattering spectroscopy has been used for the characterization of zinc oxide nanoparticles obtained by mechanical activation in a high-energy vibro-mill and planetary ball mill. Raman modes observed in spectra of nonactivated sample are assigned to Raman spectra of the ZnO monocrystal, while the spectra of mechanically activated samples point out to the structural and stoichiometric changes, depending on the milling time and the choice of equipment. Observed redshift and peak broadening of the E 2 high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
173
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(202 citation statements)
references
References 41 publications
(131 reference statements)
24
173
1
4
Order By: Relevance
“…ZnO and the Li-doped ZnO materials presented identical Raman modes and relative intensities (Figure 1 e). The Raman spectra were consistent with that of standard wurtzite ZnO; [28,29] in detail, Raman modes A-D originated from second-order E 2 -low, second-order A 1 -TO, firstorder A 1 -TO, and first-order E 2 -high wurtzite ZnO, respectively. [28] Importantly, Li 2 O typically exhibits a Raman mode at about 523 cm À1 (F 2g mode), [30,31] which was absent from the Raman spectra of Li-doped ZnO, thus further substantiating the successful doping of Li in the ZnO lattice.…”
Section: Resultssupporting
confidence: 71%
“…ZnO and the Li-doped ZnO materials presented identical Raman modes and relative intensities (Figure 1 e). The Raman spectra were consistent with that of standard wurtzite ZnO; [28,29] in detail, Raman modes A-D originated from second-order E 2 -low, second-order A 1 -TO, firstorder A 1 -TO, and first-order E 2 -high wurtzite ZnO, respectively. [28] Importantly, Li 2 O typically exhibits a Raman mode at about 523 cm À1 (F 2g mode), [30,31] which was absent from the Raman spectra of Li-doped ZnO, thus further substantiating the successful doping of Li in the ZnO lattice.…”
Section: Resultssupporting
confidence: 71%
“…The first four peaks at 328, 379, 413, and 437 cm -1 are attributed to the E 2H -E 2L , A 1 (TO), E 1 (TO), E 2 (high) modes, respectively [23,24]. It can be observed that the E 2 (high) mode has the strongest intensity for both samples, which confirms that the synthesized samples have a good crystal quality of hexagonal wurtzite phase [22,23]. The E 1 (TO) and A 1 (TO) reflect the strength of the polar lattice bonds [24].…”
Section: Micro-raman Scatteringsupporting
confidence: 70%
“…Zone center optical phonons predicted by group theory are A 1 +2E 2 +E 1 , where A 1 and E 1 modes are polar and split into the transverse optical (TO) and longitudinal optical (LO) phonons. In addition, the E 2 mode consists of two modes: E 2 high which is associated with the vibration of oxygen atoms, and E 2 low which is associated with the Zn sublattice [21][22][23] . The effect of annealing temperature evolution shows that the major difference between the Raman spectra of samples annealed at 500 ºC and 700 ºC is the appearance of E 2 high mode at 438 cm -1 .…”
Section: Resultsmentioning
confidence: 99%